Early ontogenesis indexes of suckling cattle and possibility of their use for increase the productivity of suckling herds - Вацький, В. Ф.; Величко, С. А. (Scientific Progress & Innovations, 2013)
The features of connection of embryo development indexes of calves with the level of their next suckling productivity as first-calf cow are studied. It is set that more productive cows are characterized by less mass at birth, but a difference is not reliable. Short and middle duration of embryo development is instrumental in the display of high milk productivity. Using of indexes of embryo speed of growth and relation of calf birth mass to mass of mother next to the indexes of duration of embryo development and birth mass during the estimation of organism individual features allows to find more productive cows immediately after their birth.